(untitled) (Third Sector Social Economic Review, 2020)
As a result of migration movements from Syria to Turkey since 2011, the number of Syrian refugees under temporary protection in Turkey has approached four million according to official figures. Due to the increase in the number of Syrian refugees, legal arrangements were made in 2013, allowing them to benefit from public services. With the arrangements made, children of Syrian refugees were included in the education process in public schools, but as a result some problems emerged in the education process. The purpose of this study was to determine the problems experienced in the primary schools where the Syrian students are educated in terms of the teachers’, the school administrators’, the Syrian parents and students’ perspectives. The data were obtained from 63 teachers, 9 school administrators, 28 Syrian students’ parents and 31 Syrian students, using the interview technique, which is one of the qualitative research methods. The data obtained was analyzed by descriptive analysis method. The main problems in schools where Syrian students are educated were classified and discussed under the main themes, which are communication, education process, classroom climate, physical structure of the school, school attendance, registration, behavior, cultural differences, bullying-exclusion and otherization, academic success.